Anxiety sensitivity and anxiety as correlates of expected, experienced and recalled labor pain - Čuržik, Doris (Array, 2011)
There has been a good deal of research on the role of anxiety sensitivity in pain perception, but only recently have investigators begun to assess its role in labor pain. The aim of this study was to investigate the nature of this relationship as well as the relationship of state and trait anxiety with labor pain. Assessments of maximum and average labor pain were completed in three different time periods (before, during and immediately after labor, and 1 month postpartum). Anxiety and anxiety sensitivity measures were completed during the late stage of pregnancy. A total of 46 primiparous healthy pregnant women, carrying a single child, participated in the study. State anxiety correlated significantly with maximum (r=0.352, p<0.01) and average (r=0.325, p<0.05) labor pain expectancies, whereas trait anxiety correlated significantly with maximum labor pain expectancies (r=0.306, p<0.05). During labor, only the physical concerns dimension of anxiety sensitivity shared a significant relationship with sensory pain (r=0.292, p<0.05). In conclusion, anxiety shares a significant relationship with labor pain expectancies only, whereas the physical concerns dimension of anxiety sensitivity correlates significantly with sensory pain during labor. These data clarify the role of anxiety and anxiety sensitivity in the experience of labor pain. Clinical implications are discussed.